Efficacy and safety of heat-sensitive moxibustion in the treatment of ulcerative colitis: A protocol for a systematic review and meta-analysis. Issue 4 (29th January 2021) - Wang, Jinlong; Zhang, Quanhui; Deng, Yongwen; Deng, Gen; Huang, Feihong; Zhou, Yiduo; Jia, Mingyan; Yi, Haoran
Abstract: Background: Ulcerative colitis (UC) is a chronic nonspecific intestinal inflammatory disease with unclear etiology occurring in the colonic mucosa. Its clinical manifestations are characterized by recurrent abdominal pain, diarrhea, mucous pus, and blood stool. The severity of the disease varies, and itis characterized by a high recurrence rate. Because of its long course of disease, easy to relapse, protracted and difficult to recover, seriously affect the quality of life, increase the economic burden of patients and society, and even the risk of developing cancer, it has become one of the hot issues of general concern in the medical field. Heat-sensitive moxibustion therapy has shown strong advantages in the treatment of UC, and the curative effect is accurate. therefore, this paper will carry out a systematic evaluation and meta analysis of the efficacy and safety of heat-sensitive moxibustion in the treatment of UC. Methods: We will be searching 8 electronic databases, including PubMed, Embase, Web of Science, Cochrane Library, the China National Knowledge Infrastructure, Chinese Science and Technology Periodical Database, Wanfang Database, and Chinese Biomedical Literature Database. We will search above electronic databases from the beginning to December 2020, without any language restriction. Clinical efficacy, including total effective rate or cure rate, clinical symptom integral (abdominal pain, diarrhea, purulent stool), and recurrence rate will be accepted as the primary outcomes. The changes of cytokine Hs-CRP, IL-6, TNF-αlevels in serum, and improvement of colorectal mucosa will be used as secondary outcomes. RevMan 5.3 software will be used for statistical analysis. The result about the curative effect and safety of heat-sensitive moxibustion for UC will be presented as risk ratio for dichotomous data and mean differences with a 95% confidence interval for continuous data. Results: When this research program is completed, the relevant results can be obtained. Conclusions: The results of this study will provide reliable evidence for the efficacy and safety of heat-sensitive moxibustion in the treatment of UC. INPLASY Registration number: INPLASY20201101034.